Collecting migrants' Facebook posts: Accounting for ethical measures in a text-as-data approach - Dedecek Gertz, Helena (Frontiers in Sociology, 2023)
Based on the heuristics proposed by Nissenbaum (2010) to assess ethical issues surrounding research using new technologies, this paper discusses how to justify the collection and analysis of migrants’ digital traces for academic research purposes. Specifically, our analysis is grounded in the case of an empirical paper (Authors, forthcoming) that applies a topic modeling approach to a large dataset of migrants’ posts written on Facebook groups. After discussing the nine aspects proposed by Nissenbaum (2010), we contend that while researchers can strive to comply with ethical measures by, for instance, asking adequate questions and protecting the collected data, the lack of transparency put forth by social networking sites is harmful to critical social sciences research (Bruns, 2019) and can hamper findings that can contribute to understanding migratory patterns and decisions.